1, 3, 5-Triazine and carbazole derivatives for OLED applications. (February 2018) - Zassowski, Pawel; Ledwon, Przemyslaw; Kurowska, Aleksandra; Herman, Artur P.; Lapkowski, Mieczyslaw; Cherpak, Vladyslav; Hotra, Zenon; Turyk, Pavlo; Ivaniuk, Khrystyna; Stakhira, Pavlo; Sych, Galyna; Volyniuk, Dmytro; et al.
Abstract: Series of compounds consisting of carbazole arms and 1, 3, 5-triazine core linked by amino group were synthesized and characterized. The clear relationship between electrochemical properties, quantum efficiency, charge transport properties and structure were estimated. The exciplex-forming properties of the synthesized compound as donor, and two known exciplex-forming acceptors 4, 7-diphenyl-1, 10-phenanthroline (Bphen) and 2, 2′, 2"-(1, 3, 5-benzenetriyl)-tris(1-phenyl-1-H-benzimidazole) (TPBi) where predicted and investigated. It was shown that the star-shaped configuration of the compound 3CzNCprovides the best exciplex OLED performance with EQE up to 6.84%. Graphical abstract: Highlights: The slight modification of compounds structure significantly change its properties. The performance of OLEDs based on star-shaped compound is significantly better in comparison to linear analogous. Efficient emission with EQE up to 6.84% from interlayer exciplexes was achieved.